Market Watch: Information and Availability Cascades Among the Media and Investors in the U.S. IPO Market - Pollock, Timothy G.; Rindova, Violina P.; Maggitti, Patrick G. (Academy of Management Journal, 2008)
In this study we advance current research on social influence in markets by examining how the recency and availability of information about others' actions within and between different communities influence their allocation of attention and their evaluations. Specifically, we examine how the media and investors allocate attention to and evaluate newly public firms in the days following their initial public offerings (IPOs). Our findings have implications for understanding the fieldwide processes through which the value of new firms is established in markets.